Pedagogical Paradigm Shift: Integrating Soft Skills into English Language Teaching - Paneru, Narendra Raj (ILAM इलम, 2024)
This article aims to explore the shift in pedagogical paradigms in English language instruction through educators' understanding of soft skills and the challenges associated with integrating them into the language teaching. For this, the study has been made by synthesizing scholarly literature, conducting empirical research, and conducting a thematic analysis of data from six English language educators of diverse colleges in the Kathmandu Valley. Additionally, it proposes a dynamic and student-centric instructional approach integrated with soft skills. Such provision also adds to the current discourse on innovative pedagogical approaches and methods in English language instruction.